Toward an Integrative Framework of PAI Curriculum Development: A Critical Analysis of Academic, Humanistic, and Social Reconstruction Approaches: (Kerangka Kerja Integratif Pengembangan Kurikulum PAI: Analisis Kritis Pendekatan Akademik, Humanistik, dan Rekonstruksi Sosial) - Sa’adah; Tobroni; Faridi (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
The Islamic Religious Education (PAI) curriculum development approach must be comprehensive and integrated to ensure that the curriculum is able to meet the needs and develop the potential of students to the fullest. The purpose of this study is to analyze the various approaches to Islamic Education curriculum development. By using qualitative research method of literature study. Curriculum development is seen as a comprehensive process in which each important element of the curriculum such as curriculum planning, curriculum implementation, and assessment plays an important role. Therefore, it is necessary to change the curriculum in accordance with the times and surrounding conditions, this is why curriculum development requires an approach. An approach to curriculum development involves applying appropriate strategies and methods and following systematic development steps. The aim is to ensure that the resulting curriculum is in line with educational needs and can provide optimal results for students. This approach includes needs analysis, planning, design, implementation and evaluation of the curriculum. With a structured approach, the curriculum can be more effective in achieving educational goals and meeting set standards. Among these approaches are the academic subject approach, the humanistic approach and the social reconstruction approach.